2020
DOI: 10.1111/jvim.16016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 3 refractometers to determine transfer of passive immunity in neonatal beef calves

Abstract: Background: Refractometry is used to assess transfer of passive immunity (TPI), but studies evaluating different refractometers and appropriate thresholds for recommended target immunoglobulin G (IgG) concentrations for beef calves are limited. Objectives: To evaluate test performance of digital (DSTP) and optical (OSTP) serum total protein (STP) refractometers and a digital Brix (DBRIX) refractometer for assessment of passive immunity in beef calves. Animals: A total of 398 beef calves from 6 herds, 1 to 7 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
19
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 37 publications
11
19
5
Order By: Relevance
“…The optimal cut-off value we ascertained in the present study for the D-Brix refractometer for the estimation of IgG concentrations of <16 g/L was similar to previously reported digital Brix percentages for IgG of <16 g/L (Gamsjäger et al, 2021;Pisello et al, 2021;Akköse et al, 2022c). The cut-off value we determined for the D-Brix refractometer for estimating IgG concentrations of <24 g/L was higher than the digital Brix refractometer cut-off value previously reported by Gamsjäger et al (2021) and lower than the digital Brix refractometer cut-off value previously reported by Akköse et al (2022c). The cut-off value ascertained for the O-Brix refractometer for estimating IgG concentrations of <16 g/L was similar to the optical Brix refractometer cut-off value reported by Pisello et al (2021).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The optimal cut-off value we ascertained in the present study for the D-Brix refractometer for the estimation of IgG concentrations of <16 g/L was similar to previously reported digital Brix percentages for IgG of <16 g/L (Gamsjäger et al, 2021;Pisello et al, 2021;Akköse et al, 2022c). The cut-off value we determined for the D-Brix refractometer for estimating IgG concentrations of <24 g/L was higher than the digital Brix refractometer cut-off value previously reported by Gamsjäger et al (2021) and lower than the digital Brix refractometer cut-off value previously reported by Akköse et al (2022c). The cut-off value ascertained for the O-Brix refractometer for estimating IgG concentrations of <16 g/L was similar to the optical Brix refractometer cut-off value reported by Pisello et al (2021).…”
Section: Discussionsupporting
confidence: 88%
“…Our study compared the diagnostic accuracy of optical and digital Brix refractometers in predicting different passive immunity statuses in beef calves. To date, only very few studies have assessed digital Brix percentages indicative of serum IgG of <16 g/L (Gamsjäger et al, 2021;Pisello et al, 2021;Akköse et al, 2022c) or <24 g/L (Gamsjäger et al, 2021;Akköse et al, 2022c). On the other hand, there is no report on optical Brix percentages indicative of serum IgG of <24 g/L.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Similarly, the median serum Brix of calves at 48 hours of life (NO-VACC, 10.9%; VACC, 10.6%) was adequate and consistent with what is considered excellent transfer of passive immunity in beef calves. 27 Results from previous studies 28,29 have demonstrated that the greater the initial virus-specific serum antibody titer transferred from colostrum, the longer the duration of specific immunity in calves. Other studies 30,31 suggest that vaccination of cows during the last trimester of gestation with inactivated-virus vaccines results in greater deposition of specific antibodies in maternal colostrum and greater initial BVDV and BHV-1 serum antibody titers in their calves.…”
Section: Discussionmentioning
confidence: 92%
“…Only the performances for the category of poor TPI could be directly compared with other studies using a dichotomous standard with cut-off value equivalent to 10 mg/mL IgG. The sensitivity of the Brix refractometer for this category (0.69) was lower than that reported in many other studies in the literature (e.g., 0.87 [27], 0.88 [18], 0.81 [45]). One reason might be the different Brix cut-off values in these studies that were usually optimized (e.g., using ROC curves) to obtain the best results.…”
Section: Qualitative Analysesmentioning
confidence: 99%